Parents’ Parenting Awareness and Depressive Symptoms in Treatment-Referred Youth - Boughton, Kristy L.; Bailey, Heidi N.; Lumley, Margaret N. (Canadian Journal of Counselling and Psychotherapy, 2016)
Research links parenting to youth psychopathology, yet scant research has considered the child, parent reports, and observational measures of parenting to elucidate the complex patterns of risk. This study investigates how the interaction of parents’ own reports and observations of parenting relate to youth depressive symptoms. Parents whose self-reports were most discrepant from their observed parenting had children with higher depressive symptoms. Awareness or acknowledgement of one’s own parenting may be one consideration for the impact of parenting on youth functioning, and contrasting observed parenting with family members’ reports may make a valuable contribution to the assessment and treatment of youth.